Improving Students' Writing Skill by Using Pictures in Vocational High Schools - Pramilaga, Ni Made; Putra, I Nyoman Adi Jaya; Suprianti, G.A.P. (Universitas Pendidikan Ganesha, 2023)
This research highlights students' struggles in developing and organizing ideas in descriptive writing, along with the lack of attention from teachers regarding students' comprehension of the taught material. The study aims to analyze the improvement of writing skills among tenth-grade students through the integration of images as visual aids. Employing a mixed-methods approach, qualitative data was gathered through classroom observations, interviews, and journals, while quantitative data was obtained through pre- and post-assessments. The subjects involved in this research are the tenth-grade students integrated with images as visual aids to enhance their writing skills. The findings indicate that the positive use of images impacts students' engagement, motivation, and creativity in writing, leading to a significant improvement in the quality of their compositions. The effectiveness of innovative teaching strategies and the value of visual aids in supporting students' writing learning processes are the main focal points. This article underscores the importance of a mixed-methods approach for a comprehensive understanding of pedagogical interventions in education. The research provides deep insights into the role of images as stimuli in enhancing students' writing skills while emphasizing the need for innovative pedagogical approaches in educational contexts. Furthermore, the implications of these research findings emphasize the urgency of using visual aids in teaching, contributing significantly to enhancing the quality of classroom learning.